Introduction to AI and Computational Thinking for Teachers at SDIT Mafatih Bekasi - Linda Nur Afifa; Adam Arif Budiman; Aji Setiawan; Afri Yudha (JEPTIRA, 2025)
The development of Artificial Intelligence (AI) and the demand for strengthening Computational Thinking (CT) skills make AI and CT literacy a key competency for educators in the 21st century. At the elementary level, particularly in Integrated Islamic Elementary Schools (SDIT), teachers play a crucial role in instilling systematic thinking and technological literacy from an early age, yet many teachers lack conceptual understanding or practical skills related to AI and CT. This community service activity aims to improve SDIT teachers' basic understanding of AI concepts, examples of AI applications in education, and the CT process and its implementation in elementary school learning activities. The activity was carried out in the form of face-to-face training that included material presentations, demonstrations of educational AI applications, and practical CT activity designs tailored to the characteristics of elementary school students. Evaluation was conducted using pre- and post-tests to measure knowledge gains, and questionnaires to assess participants' perceptions and satisfaction levels. The implementation results showed an increase in participants' knowledge scores between before and after the training, accompanied by a more positive change in attitudes towards the use of AI and CT in the classroom. Teachers were also able to design simple and contextual CT-based learning activities for elementary school students. This activity shows that structured training with a combination of conceptual material and directed practice is effective in building AI and CT literacy among SDIT teachers.